تحليل المردودية في المؤسسات الاقتصاديةDUPONTتقييم الاداء المالي حسب نموذج - شيماء لعلايبية; يسمينة قاضي ولاء (My University, 2022)
This study aims to investigate the extent to which the DuPont model for profitability analysis can contribute to evaluating the financial performance of the Saidal Corporation during the period (2016- 2020), by addressing the traditional and modern financial performance indicators, and then analyzing the profitability based on the DuPont model, which necessitated the use of the approach The descriptive analytical method on the one hand and the case study method on the other. The results of evaluating the financial performance of the Saidal Corporation showed that it has a good degree of independence that guarantees it permanent funding, but that it suffers from the inefficiency of its investment and operational decisions, as well as the lack of good use of its assets to generate profits, especially during the years 2018/2019, while the Corona pandemic reflected positively on the institution in the year 2020. , which is what the study also found when analyzing the components of the DuPont model, where there is a decrease in the rate of profitability of exploitation as a reflection of its commercial profitability, and the fluctuation in the turnover rate of economic assets within the components of economic profitability, while there is a decrease in thecommercial margin and a noticeable increase in the rate of debt within the components of financial profitability. This is primarily due to the increase in net investments and the expansion of the Corporation's activity .................................................... تهدف هذه الدراسة إلى البحث في مدى إمكانية مساهمة نموذج دوبوذنت لتحليل المردودية في تقييم الأداء المالي2016-2020(، من خلال التطرق لمؤشر الأداء المالي التقليدية منها والحديثة، ومن ثمّ - تحليل المردودية بناء على نموذج دوبونت، ما استوجب استخدام المنهج الوصفي التحليلي من جهة ومنهج دراسة الحالة من جهة أخرى. وقد أوضحت نتائج تقييم الأداء المالي لمؤسسة تم تّعها بمدى استقلالية جيد يضمن لها تمويلا دائما، إلا أنّ ا تعاني من عام كفاءة قراراتها الاستثمارية والتشغيلية كذلك عدم استغلالها الجيد لأصولها في توليد الأرباح خاصة خلال 2011 ، بينما انعكست جائحة كورونا إيجابا على المؤسسة سنة 2020 ، وهو ما توصّلت له الدراسة أيضا / سنتي 2012 عند تحليل مركّبات نموذج دوبوذنت، حيث هناك انحفاض في معاّير ربحية الاستغلال كانعكاس لمردوديتها التجارية، وتذبذب معا دوران الأيول الاقتصادية ضمن مركّبا المردودية الاقتصادية، بينما هناك انحفاض في الهامش التجاري وارتفاع ملحوظ في الاستبانة ضمن مركّبا المردودية المالية، ويعود ذلك بالدرجة الأولى لتزايد الاستثمارا الصافية وتوسع نشاط المجمّع..